IT tools for the management of multi - representation geographical information - Falchi, Ugo (International Journal of Engineering and Technology, 2018)
The goal of this research was the creation of software tools for managing instances of a multi - representation geodatabase, able to define multiple representations and topological constraints, in relation to modeled objects and structures according to the classification of the Italian national technical specifications of the November 10, Italian Ministerial Decree 2011. After the development of a conceptual scheme, encoded in its corresponding logical mode, various computer artifacts were designed and developed from scratch to perform the upload, management and display of data: a Scheme Designer, which allows users to define the logical model and implement the physical model of an instance of Oracle; a Loader, which allows users to populate the database; a GUI, which is a graphical interface to the tools and Schema Designer Loader; a DB Navigator, which is the web interface to the database multi - representation.